Innovation to the core : a blueprint for transforming the way your company innovates - Skarzynski, Peter; Gibson, Rowan (Boston, Mass. : Harvard Business School Press, 2008)
Building on the work of strategy guru Gary Hamel, this guide shows organizations how to move innovation from a buzz word to a core competency. Skarzynski, a consultant on international growth and strategy, and Gibson, a global business strategist, draw on a wealth of examples from real companies including GE, Procter & Gamble, Nokia, and IBM. They provide frameworks, step-by-step action lists, and other practical tools for improving an organization's capacity for innovation by mobilizing the imagination of employees, customers, and business partners.
The new innovation challenge -- Creating the preconditions for innovation -- Building a foundation of novel strategic insights -- Producing a torrent of new opportunities -- Innovating across the business model -- Asking the right questions at the right time -- Constructing an innovation architecture -- Managing and multiplying resources -- Pacing and derisking innovation investments -- Dynamically balancing supply and demand -- Building a systemic innovation capability -- Making innovation sustainable.
Includes bibliographical references (pages 277-278) and index.
English.
Print version record.
Keywords: Organizational effectiveness; Organizational change; Leadership; Efficacité organisationnelle; Changement organisationnel; Leadership; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Leadership; Organizational change; Organizational effectiveness; Führung; Innovationsmanagement; Organisationswandel; elektronické knihy; electronic books